Emansipasi Sebagai Tata Bahasa Telaah Filsafat Moral Axel Honneth tentang Multikulturalisme - Alexander Seran (Arete, 2013)
This article is concerned to show Axel Honneth’s philosophical approach that explains the struggle for the establishment of relations of mutual recognition, as a precondition for self-realization. Like G.W.F.Hegel, G.H. Mead, and many feminist proponents, Honneth stresses the importance of social relationships to the development and maintenance of a person’s identity. Honneth develops a framework for interpreting social struggles based on common values. The moral philosophy of Honneth can be applied in interpreting Pancasila as universal principles that must be reflected in positive-lawmaking. Therefore the constitution and rules or regulations that are based on the constitution can be amended to meet society’s needs and demands.